The Saccharomyces cerevisiae DNA polymerase alpha catalytic subunit interacts with Cdc68/Spt16 and with Pob3, a protein similar to an HMG1-like protein. - Wittmeyer, J (1997)
We have used DNA polymerase alpha affinity chromatography to identify factors involved in eukaryotic DNA replication in the yeast Saccharomyces cerevisiae. Two proteins that bound to the catalytic subunit of DNA polymerase alpha (Pol1 protein) are encoded by the essential genes CDC68/SPT16 and POB3. The binding of both proteins was enhanced when extracts lacking a previously characterized polymerase binding protein, Ctf4, were used. This finding suggests that Cdc68 and Pob3 may compete with Ctf4 for binding to Pol1. Pol1 and Pob3 were coimmunoprecipitated from whole-cell extracts with antiserum directed against Cdc68, and Pol1 was immunoprecipitated from whole-cell extracts with antiserum directed against the amino terminus of Pob3, suggesting that these proteins may form a complex in vivo. CDC68 also interacted genetically with POL1 and CTF4 mutations; the maximum permissive temperature of double mutants was lower than for any single mutant. Overexpression of Cdc68 in a pol1 mutant strain dramatically decreased cell viability, consistent with the formation or modulation of an essential complex by these proteins in vivo. A mutation in CDC68/SPT16 had previously been shown to cause pleiotropic effects on the regulation of transcription (J. A. Prendergrast et al., Genetics 124:81-90, 1990; E. A. Malone et al., Mol. Cell. Biol. 11:5710-5717, 1991; A. Rowley et al., Mol. Cell. Biol. 11:5718-5726, 1991), with a spectrum of phenotypes similar to those caused by mutations in the genes encoding histone proteins H2A and H2B (Malone et al., Mol. Cell. Biol. 11:5710-5717, 1991). We show that at the nonpermissive temperature, cdc68-1 mutants arrest as unbudded cells with a 1C DNA content, consistent with a possible role for Cdc68 in the prereplicative stage of the cell cycle. The cdc68-1 mutation caused elevated rates of chromosome fragment loss, a phenotype characteristic of genes whose native products are required for normal DNA metabolism. However, this mutation did not affect the rate of loss or recombination for two intact chromosomes, nor did it affect the retention of a low-copy-number plasmid. The previously uncharacterized Pob3 sequence has significant amino acid sequence similarity with an HMG1-like protein from vertebrates. Based on these results and because Cdc68 has been implicated as a regulator of chromatin structure, we postulate that polymerase alpha may interact with these proteins to gain access to its template or to origins of replication in vivo.